Infantile allergic diseases: a cohort study prenatal fish intake and mercury exposure context - Surabhi Shah; Hae Soon Kim; Yun-Chul Hong; Hyesook Park; Mina Ha; Yangho Kim; Ji Hyen Lee; Eun-Hee Ha (BMC Public Health, 2024)
Abstract Background Allergic diseases (ADs) have been increasingly reported in infants and children over the last decade. Diet, especially the inclusion of fish intake, may help to lower the risk of ADs. However, fish also, can bioaccumulate environmental contaminants such as mercury. Hence, our study aims to determine what effects the type and frequency of fish intake have on ADs in six-month-old infants, independently and jointly with mercury exposure. Methods This study is part of the prospective birth cohort: Mothers and Children’s Environmental Health (MOCEH) study in South Korea. Data was collected on prenatal fish intake, prenatal mercury concentration and ADs for infants aged six months for 590 eligible mother-infant pairs. Logistic regression analysis was conducted to evaluate the risk of prenatal fish intake and mercury concentration on ADs in infants. Finally, interaction between fish intake and mercury concentration affecting ADs in infants was evaluated. Hazard ratios of prenatal fish intake on ADs in 6 month old infants were calculated by prenatal mercury exposure. Results Logistic regression analysis showed that white fish (OR: 0.53; 95% CI 0.30–0.94; P < 0.05) intake frequency, once a week significantly decreased the risk of ADs in infants. Stratification analysis showed that consuming white fish once a week significantly reduced the hazard of ADs (HR: 0.44; 95% CI 0.21–0.92; P < 0.05) in infants in the high-mercury (≥ 50th percentile) exposure group. Conclusion The result indicates that prenatal white fish intake at least once a week reduces the risk of ADs in infants, especially in the group with high prenatal mercury exposure.